Expertise development of elite Taekwondo coaches - Cherifi, N.; Johnson, J. A.; Chin, S. T. (Physical Activity Review, 2021)
Objective: While numerous studies on the expertise of elite sports coaches have been conducted, few studies have been conducted on coaching Taekwondo, an Olympic sport rapidly gaining worldwide popularity. Yet, as a combat sport with Asian martial arts roots, elite Taekwondo coaches may have different needs than their peers in other sports. The present study thus explored elite Taekwondo coaches during the course of their careers. Methods: Qualitative data were gathered through semi-structured interviews. Coaches (n=9) were selected via purposeful sampling and were all elite Taekwondo coaches with more than 10 years` experience in elite Taekwondo coaching. Focused questions examined the transition of expert elite Taekwondo coaches through various stages in their careers to explore their expertise development process. Results: Five key variables emerged from the analysis of the expert coaches` growth toward expertise. These variables correlate with what other coaches of elite coaches experienced during their development, thus evidencing that coaching Olympic Taekwondo is not unlike coaching other elite sports.